Hubungan Antara Dukungan Orang Tua Dengan Hasil Belajar Peserta Didik Di TPA/TPQ Ahmad Al- Fatih Di Nagari Carocok Anau Kabupaten Pesisir Selatan - Mayuni, Wike; Irmawita, Irmawita (Jurnal Family Education, 2024)
This research is motivated by the low learning outcomes of students at TPA/TPQ Ahmad Al-Fatih in Nagari Carocok Anau, Pesisir Selatan Regency. This is due to parental support. This research aims (1) to describe the support of parents of students at TPA/TPQ Ahmad Al – Fatih Nagari Carocok Anau Pesisir Selatan Regency (2) describes the learning outcomes of students at TPA / TPQ Ahmad Al – Fatih Fatih Nagari Carocok Anau Pesisir Selatan Regency (3) looks at the relationship between parental support and student learning outcomes at TPA / TPQ Ahmad Al - Fatih Nagari Carocok Anau, Pesisir Selatan Regency. This research uses a quantitative approach with a correlational type. The research population is students at TPA/TPQ Ahmad Al - Fatih Nagari Carocok Anau, Pesisir Selatan Regency from class III, IV, totaling 50 people out of 70 % were sampled from 35 people from 30% using the Stratified Random Sampling technique. The data collection technique used a questionnaire. The data analysis technique used the Product Moment Percentage formula. Nagari Carocok Anau, Pesisir Selatan Regency is classified as low, this can be and is proven from the results of the questionnaire data that has been conducted (2) Picture of student learning outcomes at TPA/TPQ Ahmad Al- Fatih in Nagari Carocok Anau, Pesisir Selatan Regency is in the low category. This can be observed through learning outcomes (3) There is a significant relationship between parental support and learning outcomes at TPA/TPQ Ahmad Al-Fatih in Nagari Carocok Anau, Pesisir Selatan Regency.